Pengembangan Diri Sebagai Fasilitator Belajar Pada Program Education Di Sentul Bogor - Widiastuti tc; Yubali Ani, Ashiong Parhehean Munthe (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2019)
This activity is a continuation of the collaboration that began from the 2018-2019 term I academic year between the Pelita Harapan PGSD-FIP and the Emmanuel Foundation. Activities carried out include; this training is dedicated for learning facilitators to be able to teach creatively and practice their teaching skills at the location of their learning community. The objectives of the training activities are: 1) developing high school students themselves as learning facilitators; 2) lead learners who learn; 3) able to solve problems (problem solver), both for themselves and the environment; 4) being a creative learner; 5) excel in learning achievement; 6) direct practice in the learning community they lead. Implementation of activities in the form of training, including: 1) the provision of material; 2) question and answer session; 3) designing learning plans, making teaching aids, and compiling an assessment of the learning done; 4) games in groups with mentors; and 5) the practice of teaching directly individually in accordance with the plan for implementing the learning they have arranged. The activity takes place from July to December 2018, every Saturday 2 times a month. The training activities are provided help students have knowledge in the field of teaching, such as planning a lesson, making teaching aids, making simple judgments, and carrying out learning. Keywords: development, facilitator, problem solver, learning community